2011
DOI: 10.1097/aud.0b013e31820512bb
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Load During Speech Perception in Noise: The Influence of Age, Hearing Loss, and Cognition on the Pupil Response

Abstract: The pupil response systematically increased with decreasing speech intelligibility. Ageing and hearing loss were related to less release from effort when increasing the intelligibility of speech in noise. In difficult listening conditions, these factors may induce cognitive overload relatively early or they may be associated with relatively shallow speech processing. More research is needed to elucidate the underlying mechanisms explaining these results. Better TRTs and larger word vocabulary were related to h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

36
364
3
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 339 publications
(426 citation statements)
references
References 69 publications
36
364
3
2
Order By: Relevance
“…Similar to the current data, Zekveld et al (2011b) showed that better ability to read masked text was related to more cognitive processing load during sentence perception in noise as assessed by examination of the pupil response. These and the current data may suggest that participants with high TRT ability may use a particular strategy in both the TRT and speech perception tests that, although effortful, increases their performance over that observed in low-TRT individuals.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Similar to the current data, Zekveld et al (2011b) showed that better ability to read masked text was related to more cognitive processing load during sentence perception in noise as assessed by examination of the pupil response. These and the current data may suggest that participants with high TRT ability may use a particular strategy in both the TRT and speech perception tests that, although effortful, increases their performance over that observed in low-TRT individuals.…”
Section: Discussionsupporting
confidence: 72%
“…Based on the 'neural efficiency hypothesis ' (Neubauer & Fink, 2009) and the predictions of the ELU framework, we expected that larger WM capacity will be associated with less activation in left IFG areas. Based on Zekveld et al (2011b), we predicted greater activity in left IFG regions, reflecting greater processing load, in listeners with better TRT performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The eye tracking system was calibrated based on neural network to correct the geometry distortion of pupillary response data. Zekveld et al (2011) evaluated the influence of age, hearing loss, and cognitive ability on the cognitive load during listening to speech presented in noise. Cognitive load was assessed by examination of pupil dilation.…”
Section: Noisy Factors In Workload Measuresmentioning
confidence: 99%
“…Considering that the neural tracking of attended speech in older listeners improved more than that of younger when reducing the spectro-temporal degradation of the auditory signal (Presacco et al, 2016), it might have been expected that listeners with worse hearing would experience a larger benefit from reducing the external degradation. However, a previous study has observed a similar reduced sensitivity towards improvements in the speech intelligibility in the pupil-data of elderly hearing-impaired listeners compared to younger and age-matched normal-hearing listeners (Zekveld et al, 2011). Zekveld and colleagues suggested that the observation could result from speech processing being more superficial for the listeners with worse hearing (Zekveld et al, 2011).…”
Section: Neural Effects Of Altering the Background-noise Levelsmentioning
confidence: 82%